1893 Neb. Comp. Stat. 393 - (:unkn) unknown (My University, 1893)
Ch. 47, § 3: It shall also be unlawful for any person, at any time, by the aid or use of any swivel, punt gun, big gun (so called), or any other than the common shoulder gun; or by the aid or use of any punt boat, or sneak boat used for carrying such gun, to catch, kill, wound, or destroy, or to pursue after with intent to catch, kill, wound or destroy upon any of the waters, bays, rivers, marshes, mud flats, or any cover to which wild fowl resort within state of Nebraska, any wild goose, wood duck, teal, canvas-back, bluebill, or other wild duck, or to destroy or disturb the eggs of any of the birds above named
Keywords: HUNTING REGULATION